Analysis of Factors Influencing Farmers' Decision to Become Community Business Entrepreneurs in Surat Thani Province - Chodchuang , Siripat; Chantanaphant , Jirayuth; Duangjan, Chompunoot (Journal of International Studies, Prince of Songkla University, 2025)
This article aims to study motivational factors affecting the decision to become a community business entrepreneur among farmers, based on data collected from a sample group of 266 individuals in Surat Thani province through purposive sampling. The data was evaluated using Exploratory Factor Analysis (EFA) and multiple regression analysis. The study identified eight factors, including leadership, knowledge and skills, training, income level, family support, government support, facilities/Infrastructure, and independence. The study of the relationship factors affecting the decision to become a community business entrepreneur among farmers revealed that the most significant factor was leadership, followed by independence. The predictive power was 51.3%, which was statistically significant at the 0.05 level. The results of this research can be used as a guideline for planning and policy management in various important factors that affect the decision-making of becoming a community business entrepreneur. This is to ensure that farmers become capable entrepreneurs, with an increasing number of them.